Mistyczki ciało w przekazie „Septililium beatae Dorotheae Montoviensis” Jana z Kwidzyna. Traktaty „De caritate” i „De Eucharistia” - Janus, Katarzyna (Studia Theologica Varsaviensia, 2018)
Mystic Woman’s Body in the Work Septililium beatae Dorotheae Montoviensis by Jan of Kwidzyn. Treatises: De caritate and De Eucharistia - Summary The purpose of this article is to present the character of Blessed Dorothy of Mątowy whose mystic experiences were down written by John of Kwidzyn. The treatises entitled De caritate and De eucharistia are part of the work Septililium beatae Dorotheae Montoviensis. Attention was paid to these two texts because the way of reflection, imagery and vocabulary of the treatises situate this mystic woman in the stream of medieval European women’s mysticism close to that of Mechtilde of Hackeborn or Saint Bridget of Sweden. The mystic experiences of Dorothy of Mątowy analysed in the context of human corporeality and sensuality enable us to draw a conclusion on the value of human body said to be a temple of the Holy Spirit. It should be stressed that although a mystic experience involves psyche, we can describe it using only words connected with corporeal, sensual experiences. In the article’s deliberations every effort was made to show a dialogue with the tradition undertaken in the treatises by John of Kwidzyn and to explain their theological and cultural contexts.